Use of the Digital Report Application for Raudhatul Athfal (ARDIRA) in Evaluating Child Growth and Development - Ruliana Fajriati; Aninditya Sri Nugraheni (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2021)
In this digital era, teachers must be able to keep up with the flow of technological developments that are so fast, because technology is a necessity that we cannot avoid. For this reason, the Ministry of Religion through the Directorate General of Islamic Education launched a Digital Report Application for Raudhatul Athfal which was later shortened to ARDIRA to make it easier for teachers to manage evaluations of children's growth and development. This study aims to determine the use of the ARDIRA application in evaluating children's growth and development, using descriptive qualitative research methods. The results of this study indicate that the use of the ARDIRA application in evaluating the growth and development of children in RA Ummi Zainab has been carried out well by the guidelines for the use of the ARDIRA application although there are still some obstacles and shortcomings in its implementation.Keyword : ARDIRA, Evaluation, Growth and Development